PENERAPAN PEMROSESAN DATA BARANG MASUK DAN BARANG KELUAR PADA GUDANG PT PLN (PERSERO) UP2D S2JB BERBASIS SITUS WEB - Aprani, Solihin; sobri, muhammad (Al Ihsan Smart Cendekia, 2025)
PT PLN (Persero) UP2D S2JB is one of the distribution management units that has a warehouse to store operational goods. In the management of the warehouse,the recording of incoming and outgoing goods data is still done manually, whichresults in frequent recording errors and difficulties in monitoring the stock of goods. Therefore, a system is needed that can facilitate the processing ofincoming and outgoing goods data effectively and efficiently. This research aimsto design and build a website-based application that can manage data on incoming and outgoing goods in the warehouse of PT PLN (Persero) UP2D S2JB. The application is built using the Waterfall software development method,which consists of the stages of analysis, design, implementation, testing, and maintenance. The technologies used in the development of this application include the PHP programming language, CSS, MySQL database, and the Bootstrap 4 framework. The result of this research is a website-based applicationthat can record and monitor data on incoming and outgoing goods more accurately and efficiently